Therapeutic Interventions of Novel SGLT2 Inhibitors Against Metabolic Disorders: Transforming the Association into Perspectives - Irshad, Kanwal; Akash, Muhammad S. H.; Rehman, Kanwal; Sharif, Hina (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Sodium-glucose co-transporter 2 (SGLT2) inhibitors are an emerging group of therapeutic agents that show their tremendous glucose lowering activity without producing hypoglycemia, which is one of the major drawbacks of existing antidiabetic therapy. Comprehensive literature was searched in English using electronic databases including PubMed, ScienceDirect, Medline, Scopus and Embase. SGLT2 inhibitors reduce blood glucose levels by producing glucosuria via insulin-independent pathway. The major mechanism by which SGLT2 inhibitors are involved in glucose homeostasis is to prevent the reabsorption of glucose in the proximal convoluted tubule and increase glucose excretion in the urine. Deterioration of β-cells, impairment of functions and development of insulin resistance do not affect the efficacy of SGLT2 inhibitors. SGLT2 inhibitors significantly reduce HbA1c, ameliorate glycemic control and control body weight. SGLT2 inhibitors can block Na+/H+ exchanger (NHE) 1 and play a significant role in treatment of heart failure especially in diabetic patients. They have also positive effects on different metabolic syndromes which cumulatively ameliorate the risk factors for cardiovascular diseases in diabetic patients. SGLT2 inhibitors can improve kidney function by reducing inflammation and improving renal microvasculature up to its original state. The increase in triglyceride level has a strong relationship with coronary artery disease in diabetic patients when combined with other indicators of metabolic disorders while SGLT2 inhibitors cause a significant reduction in plasma triglyceride level in diabetic patients. We have comprehensively summarized the features, mechanism of action of SGLT2 inhibitors and their impact on various metabolic syndrome traits, including diabetic condition, renal dysfunctioning, arterial stiffness, hypertension, lipid profile and cardiovascular diseases. The aim of this review to examine the safety, efficacy and therapeutic properties of SGLT2 inhibitors in renal and diabetic patients.
Keywords: SGLT2 inhibitors